Dynamics of Arabic language learning methods and its challenges: Case study at At-Tajdid Cepu Islamic Boarding School - Romadhon, Nur Naria Dina; Mustofa, Bisri; Al Anshory, Abdul Muntaqim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Examining the dynamics of Arabic language teaching methods in Islamic boarding schools is essential for understanding the integration of traditional and modern approaches in addressing the challenges of the digital era. This study explores how pesantren adapt to technological innovations and identifies existing challenges. The research employs a qualitative method with a case study approach, allowing the researcher to gain an in-depth understanding of complex phenomena and uncover how teaching methods are applied and evolve in the digital age. The analyzed data includes observations, interviews, and documentation. The research was conducted at Pondok Pesantren At-Tajdid Cepu. The findings indicate that: (1) The dynamics of Arabic language teaching methods at Pondok Pesantren At-Tajdid Cepu reflect an integration of developments ranging from traditional to modern methods. This transformation aims to balance Arabic language theory and practice, enhance students' motivation, and create relevant learning experiences in the digital era. (2) Arabic language learning faces internal challenges, such as limited facilities, teacher competency, and student motivation, as well as external challenges, including technological advancements and curriculum changes. To address these issues, the pesantren has improved teacher training, facilities, contextualized curriculum, external collaborations, and the use of technology to create more effective and relevant learning. The findings of this study can serve as a reference for developing relevant and effective Arabic language education.